Students’ Writing Ability by Using Freewriting Technique - Yuricki, Effrina (Lentera: Jurnal Ilmiah Kependidikan, 2022)
The aim of this research was to enhance students’ writing ability of the eighth grade through the utilization of Freewriting technique. This research is classified as classroom action research (CAR). the subjects of this research were the eighth grade students of SMP Negeri 2 Gunung Agung Tulang Bawang Barat in the academic year of 2020/2021. The data was analyzed using descriptive statistics and quantitative data analysis. This study was conducted in two cycles, each cycle consisting of four sessions. Based on the analysis of the survey, students improved their writing ability by using free writing techniques based on cycle 2 quantitative and qualitative data. The average score for cycle 1 was 60.38, but for cycle 2 it was 70.86. Moreover, this improvement can also be seen from qualitative data, such as the results of the students’ observation sheet from cycle 1 to cycle 2. The mean score of cycle 1 was 6.70, while the mean score of cycle 2 was 7.32. It showed that the students seemed to be more confidence and motivated began to write. Therefore, it can be concluded that the implementation of Freewriting technique can improve students’ writing ability and activity.